Pengaruh Model Manajemen Pembelajaran Berbasis Steam terhadap Kemampuan Literasi Digital dalam Pendidikan IPS - Muliana Muliana; Suhelayanti Suhelayanti; Nurhayati Nurhayati; Abdul Aziz; Fadhilah Fadhilah (Mudir: Jurnal Manajemen Pendidikan, 2026)
The low level of students’ digital literacy in Social Studies education has become a significant challenge in meeting the demands of 21st-century competencies. In addition, learning management practices that effectively integrate technology, creativity, and problem-solving skills into the learning process remain insufficiently implemented. This study aims to examine the effect of a STEAM-based (Science, Technology, Engineering, Arts, and Mathematics) learning management model on students’ digital literacy skills in Social Studies. The novelty of this study lies in the development of a STEAM-based learning management framework specifically designed for Social Studies education to enhance students’ digital literacy as a key 21st-century competency, whereas previous studies have primarily focused on learning outcomes or critical thinking skills within science-related disciplines. This study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 60 students, including 30 students in the experimental group and 30 students in the control group. Data were collected through tests and questionnaires that had met validity and reliability requirements. Data analysis was conducted using normality tests, homogeneity tests, N-Gain analysis, and the Independent Samples t-Test. The findings revealed that the experimental group achieved an average N-Gain score of 0.76 (high category) with an effectiveness level of 76.14%, while the control group obtained an average N-Gain score of 0.25 (low category) with an effectiveness level of 25.44%. The Independent Samples t-Test yielded a significance value of 0.000 (p < 0.05) and a t-value of 36.127, indicating a statistically significant difference between the experimental and control groups. These results demonstrate that the STEAM-based learning management model is effective in improving students’ digital literacy skills in Social Studies. Furthermore, the study indicates that learning management integrating science, technology, engineering, arts, and mathematics creates a more contextual, interactive, collaborative, and problem-solving-oriented learning environment. The model also contributes to the development of students’ critical thinking, creativity, communication, and collaboration skills. Therefore, the STEAM-based learning management model can serve as an innovative strategy for strengthening digital literacy and enhancing the quality of Social Studies education to support the development of 21st-century competencies in the era of digital transformation.